An enriched meaning of work mixed methods study on tourist guides - Ng, Yen Phin (2023)
Meaning of work (MoW) acts as a lens through which individuals interpret and react to their work. The initial dimensions of MoW orientation are job, career and calling. However, several scholars indicated that the MoW instrument was outdated and had not been improved for years. Thus, this study was motivated by the need to enrich the MoW instrument in the context of tourist guides. Tourist guides’ professions were chosen as the scope of the study due to the unique nature of the profession, which has taken on a different work meaning worth studying. Hence, the MoW instrument may not capture the whole range of meanings tourist guides assign to their work and might be beyond the existing work orientation. The study utilised a pragmatic mixed-methods approach by adopting a two-phase, exploratory sequential research design. In Phase 1, the qualitative study explored and enriched MoW dimensions by conducting semi-structured interviews with 20 tourist guides. Through thematic analysis, findings of this phase discovered three emerging variables: working atmosphere, professional contentment, and job freedom. The qualitative findings guided the development of MoW items and scales for the survey instrument. In Phase 2, 153 tourist guides participated in a quantitative study to validate the enriched MoW instrument by assessing model fit, reliability, and validity of the measurement model and structural model using Structural Equation Modelling of AMOS. The quantitative study indicated two enriched MoW dimensions, namely (i) professional contentment and (ii) job freedom were found to fit the MoW model. A total of 11 enriched measurement items emerged to represent these two dimensions, with an example of measurement items for; (i) professional contentment (6 items) is ‘I feel my job is meaningful when tourists are satisfied with my services’ and (ii) job freedom (5 items), ‘I am satisfied with the freedom to manage my job’. This study provides four contributions to knowledge. First, the expanded and enriched MoW dimensions by extending the tripartite work orientation to six dimensions for tourism industry employees. Secondly, the study expanded the MoW instrument with the inclusion of two emerging variables (mentioned earlier). This instrument may be adapted and adopted for other tourism and hospitality studies. Next, the integration of Self-Determination Theory and Person-Environment Fit Theory to explain the enriched MoW dimensions. Finally, the study applied Attribution Theory to produce a tourist guides career spectrum to distinguish and explain MoW for different career stages using five main stages. The practitioner's contributions highlight the importance of the protection of meaningful jobs and livelihoods; propose comprehensive human resource strategies and policies to improve employee attraction and retention.